Impact of oxygen flow rate on performance of indium-tin-oxide-based RRAMs. (13th May 2021) - Tsai, Tsung-Ming; Tan, Yung-Fang; Wu, Cheng-Hsien; Yang, Chih-Cheng; Chen, Wen-Chung; Lin, Chun-Chu; Wu, Pei-Yu; Zhang, Yong-Ci; Chou, Sheng-Yao; Chen, Zi-Yu; Lin, Tzu-Heng
Abstract: This paper investigates the effect of oxygen flow rates on the performance of the resistive random access memory (RRAM) of indium-tin-oxide (ITO)/ITO(O2 )/TiN configuration. By using a co-sputtering deposition system with oxygen gas at different flow rates, oxygen-rich ITO thin films, such as the RRAM switching layer, can be realized. The relationship between oxygen flow rates and electrical characteristics is provided in this research. Further, the material analyses indicate that the oxygen exhibits different bonding characteristics. As a result, the device with the lower oxygen flow rate has better electrical characteristics and reliability. In addition, to explain the experimental results, the Schottky emission conduction mechanism for the high-resistance state and the Ohmic conduction mechanism for the low-resistance state are determined through the current fitting results, and appropriate models are proposed.